Neisseria Meningitidis Serogroup Z–Induced Meningitis: The First Case from Turkey - Arga, Gül; Konca, Hatice Kübra; Çelik, Ayça Nur; Botan, Edin; Çağlayan, Utku; Özdemir, Halil; Vatansever, Göksel; Kendirli, Tanıl; Çiftçi, Ergin (Journal of Pediatric Infectious Diseases, 2022)
Neisseria meningitidis is a significant worldwide cause of bacterial meningitis and sepsis. High case-fatality rates and severe complications in survivors can occur. We present a 1-month 23-day-old case diagnosed with meningococcal meningitis and sepsis, in which serogroup Z of N. meningitidis was isolated from cerebrospinal fluid and blood cultures and treated with ceftriaxone for 7 days. Our patient is the first case of N. meningitidis serogroup Z–induced invasive meningococcal infection in Turkey. N. meningitidis serogroup Z is not included in the current meningococcal vaccines. It is concerning that a nonvaccine serogroup caused this invasive meningococcal disease and that even if the vaccine would cover this serogroup, it has happened before the usual age of administration. Therefore, meningococcal disease surveillance should continue, and an effective prevention and control strategy for nonvaccine serogroups should be implemented.
Keywords: Neisseria meningitidis; meningococcal infection; meningitis; serogroup Z